THE INFLUENCE OF ISLAMIC WORK ETHIC AND EMOTIONAL INTELLIGENCE ON JOB SATISFACTION WITH ORGANIZATIONAL COMMITMENT AS A MEDIATING VARIABLE (STUDY ON EMPLOYEES CV. MANTRA PUYANG NUSANTARA) - Ghazi, Aflah; A.Zuliansyah; Devi, Yulistia (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to investigate the influence of Islamic work ethics and emotional intelligence on job satisfaction with organizational commitment as a mediating variable. Islamic work ethic, which prioritizes the values of honesty, responsibility, and discipline, is expected to increase employee job satisfaction. In addition, emotional intelligence, which includes the ability to manage the emotions of self and others, plays an important role in creating a positive work environment and supporting job satisfaction. Organizational commitment is a factor that strengthens the relationship between Islamic work ethics and emotional intelligence to job satisfaction. This study uses a quantitative approach with survey methods on employees in CV. Mantra Puyang Archipelago. The results showed that Islamic work ethics and emotional intelligence have a significant influence on job satisfaction, both directly and through organizational commitment. These findings make an important contribution to companies in designing policies that integrate Islamic values and the development of emotional intelligence to improve employee job satisfaction.